Desirable Personnel Leadership Style of Inspector and Enforcement Office of Department of Law Enforcement, Bangkok Metropolitan Administration: รูปแบบภาวะผู้นำที่พึงประสงค์ของบุคลากร สำนักงานตรวจและบังคับการ สำนักเทศกิจ กรุงเทพมหานคร - Leetien, Kochawan (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2020)
This exploratory research objectives are study about transformational leadership, transactional leadership, and laissez-faire leadership, and comparative study personnel of inspector and enforcement office, Bangkok metropolitan administration. Representative sample in the research are from 211 persons of inspector and enforcement office, Bangkok metropolitan administration. We collect information by using 0.93 percentage of reliability questionnaire that include percentage, average, and hypothesis test by t-test and F-test (One-way ANOVA). The results revealed as these following: 1. Desirable personnel leadership style of inspector and enforcement office, Bangkok metropolitan administration’s results descending order as transformational leadership, transactional leadership, and laissez-faire leadership. 2. From the information comparison of inspector and enforcement office, Bangkok metropolitan administration about desirable personnel leadership style found that gender, age, personnel type, educational background, and works experience have an affect on difference opinions about leadership styles.